Between entrenchment, reform and transformation: ethnicity and Lebanon's consociational democracy. Issue 7 (9th November 2016) - Nagle, John
ABSTRACT: Consociationalism has become a key institutional mechanism for managing conflict after civil war. Proponents argue that a period of consociational influence can contribute to the erosion of ethnic cleavages and even a society where ethnicity is depoliticized. Critics, however, are sceptical of this claim and argue that consociationalism institutionalizes ethnic identities and stymies the transition to a healthier democracy. In response, proponents outline a liberal model of consociationalism which limits the pre-determination of ethnicity in social and political structures. Yet, problematically, consociations in postwar societies often provide guarantees of ethnic representation in order to entice belligerents to abandon violence for democracy. This issue of transitioning from a corporate consociation to a more liberal form requires sustained analysis. This paper examines this conundrum by examining contemporary Lebanese consociationalism. Given that ethnicity is central to debates about revising consociationalism, via qualitative interviews with Lebanese political elites and civil society activists, the paper analyses how these subjects conceptualize ethnicity in contrasting ways which generate different approaches to consociationalism but which ultimately frustrate meaningful reform. It does this by exploring various debates to entrench, reform or transform Lebanese consociationalism.